TBH, this may be TMI : a novel in text - Greenwald, Lisa (Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2018)
Cecily, Gabby, Prianka, and Vishal discover the need for tolerance and perfect emojis while planning a school spring fair that will hopefully make a difference.